WEB-BASED STUDENT ATTENDANCE INFORMATION SYSTEM AT MTS AL-ISHLAH PANAMBANGAN - Komarudin Komarudin (Green Publisher, 2022)
MTS Al-Ishlah Panambangan is one of the schools located in Mining, Sedong, Cirebon Regency, West Java 45189 As an educational institution, MTs AL ISHLAH Panambangan Harapan is responsive to these technological developments. With the support of human resources, this madrassa is ready to compete with other schools in public information services. Web Information Technology in particular, has become a means for MTs AL ISHLAH Panambangan to provide fast, clear, and accountable information services. From this service, schools are ready to accept suggestions from all parties which can finally answer the needs of the community. In this research paper, the author conducts an analysis of the current student attendance system. The current attendance system apparently still lacks accurate attendance data for students, because students still use conventional systems and are not carried out consistently which in the end the results of student attendance recapitulation often experience loss. To solve problems like this, the author intends to try to handle the attendance process by designing a web-based attendance information system.